Exploration of typical scenarios and application schemes of digital twin in 5G bearer network - WANG Yu; CUI Xiao; ZHU Jian; ZHOU Xiaohui; LI Fang (Dianxin kexue)
In recent years, the application of digital twin technology in the field of intelligent management and control of bearer networks has become a new hotspot and research direction. Various research institutions both domestically and internationally are exploring relevant application scenarios and conducting standardization research. Based on the current research on digital twin technology in the field of information and communication, the new challenges faced by the management and control of 5G bearer networks were analyzed, and the application scenarios and requirements of digital twin technology in 5G bearer networks were explored. Based on these typical application scenarios, the design of digital twin application service scheme and the function and data description of emulator components were proposed. Finally, an application case of 5G network slicing resource allocation and change simulation function was described.